If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + 4b + -5c = 0 Solving 3a + 4b + -5c = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4b' to each side of the equation. 3a + 4b + -4b + -5c = 0 + -4b Combine like terms: 4b + -4b = 0 3a + 0 + -5c = 0 + -4b 3a + -5c = 0 + -4b Remove the zero: 3a + -5c = -4b Add '5c' to each side of the equation. 3a + -5c + 5c = -4b + 5c Combine like terms: -5c + 5c = 0 3a + 0 = -4b + 5c 3a = -4b + 5c Divide each side by '3'. a = -1.333333333b + 1.666666667c Simplifying a = -1.333333333b + 1.666666667c
| 5y-3=12y+60 | | 14x+16=3(x-1) | | 72c-108=7c-3 | | 6x=24x+36 | | 6x-3=1.222 | | -2,992+272m=0 | | 20+2x=2.50x | | f=5+0.20d | | .778(6x-3)=2 | | 2726=29(p+35) | | 3ot-20=70 | | 16-7t=6-5t | | 3x+4-6x+2= | | -3(x-6)=-3 | | -2x^2-6x+3=0 | | 4x-3*-17=26 | | -8(2t+7)=-136 | | 25=x+x(.323) | | (4x-7)=2 | | 2(f-5)=-16 | | 52=2v+16 | | 180x+75y=165 | | -2(x^2+3x+9)+3-9=0 | | -4q-17=-6q+43 | | 10d+d-9d-d=17 | | 3x+23=-2x-7 | | 3(4x+2)=10x-2 | | 14x-5=6x+1 | | 9x+1.2=-6x+7.3 | | 2tanx=7 | | -5g+2.5=18.8 | | 3g-2g+3=12 |